Inspiring the Next Generation of Music Educators: A Multiple Case Study of High School Music Experiences and Career Choice. (July 2021) - Robison, Tiger; Edgar, Scott N.; Eros, John; Councill, Kimberly H.; Fredrickson, William E.; Helmick, Jonathan; Hoffman, Edward C.; Melago, Kathleen A.; Williams, Blair A.
The purpose of this instrumental multiple case study was to explore the roles that high school music educators and the experiences they provide play in influencing high school students' decisions to pursue a career in music education. Four bounded systems, consisting of programs led by ensemble directors with documented records and reputations for helping matriculate music education students into undergraduate music education programs, were studied. Findings were organized into the following themes: (a) formative attraction to the profession, (b) differing approaches to encouragement, (c) forms of encouragement, and (d) life as a music teacher. Specific implications for practice for multiple stakeholders and implications for future research are provided based on these findings.